EARLY WARNING SYSTEM FOR BUILDING AUTOMATION SYSTEM - Irawan, Joseph Dedy; Prasetio, Sonny; Wibowo, Suryo Adi (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2015)
Leaving the house for a long time can make the owner worry, because many problems can occur, such as fire, flood and theft so that required a security system installed in the house so the owner can find out quickly if there is interference in the house and can immediately take action. Lots of current technology that can be applied to solve these problems, in this research the equipment used to monitor and command execution is a Programmable Logic Control (PLC), using PLC as control devices can be created an early warning system, where the system will detect multiple sensors that will inform the owner via SMS if there is case of disruption in the house. Key word : buiding automation system, early warning system, PLC